Isolated Nocturnal Hypertension: What Do We Know and What Can We Do? - Tadic M; Cuspidi C; Grassi G; Mancia G (Dove Medical Press, 2020)
Marijana Tadic,1 Cesare Cuspidi,2,3 Guido Grassi,2 Giuseppe Mancia2,4 1Department of Cardiology, University Hospital “Dr Dragisa Misovic-Dedinje”, Belgrade, Serbia; 2Cardiology Department, University of Milan-Bicocca, Milan, Italy; 3Istituto Auxologico Italiano, Clinical Research Unit, Meda 20036, Italy; 4Cardiology Department, Policlinico Di Monza, Monza, ItalyCorrespondence: Marijana TadicUniversity Hospital “Dr Dragisa Misovic - Dedinje” Department of Cardiology, Heroja Milana Tepica 1, Belgrade 11000, SerbiaTel +381658107085Email marijana_tadic@hotmail.comAbstract: Nocturnal hypertension has been recognized as a significant risk factor for cardio- and cerebrovascular diseases. Blood pressure (BP) monitoring significantly increased our awareness of nocturnal hypertension and studies revealed its influence on target organ damage. Nocturnal hypertension is associated with nonphysiological 24-h BP patterns, which consider inadequate drop or even increment of nighttime BP in comparison with daytime BP (nondipping and reverse dipping). Nevertheless, investigations showed that nocturnal hypertension was a predictor of adverse outcome independently of circadian BP pattern. There are still many uncertainties regarding diagnosis, mechanisms and treatment of nocturnal hypertension. There is a small difference between American and European guidelines in cutoff values defining nocturnal hypertension. Pathophysiology is also not clear because many conditions such as diabetes, metabolic syndrome, obesity, sleep apnea syndrome, and renal diseases are related to nocturnal hypertension and nonphysiological circadian BP pattern, but mechanisms of nocturnal hypertension still remain speculative. Therapeutic approach is another important issue and chronotherapy provided the best results so far. There are studies which showed that some groups of antihypertensive medications are more effective in regulation of nocturnal BP, but it seems that the timing of drug administration has a crucial role in the reduction of nighttime BP and conversion of circadian patterns from nonphysiologic to physiologic. Follow-up studies are necessary to define clinical benefits of nocturnal BP reduction and restoring unfavorable 24-h BP variations to physiological variant.Keywords: nocturnal hypertension, nondipping, target organ damage, therapy